Football Science VII: the International Conference in Japan, 2011 - Buchheit, M.; Hopkins, W. G. (Sportscience, 2011)
The most positive aspects of this quadrennial conference were the productive mix of the various football codes and open access to videos of all 41 invited lectures. Talent Development: relative age effect, developing young players, sprint performance, draft camps. Training & Monitoring: load management, heart rate, perceived exertion, sport-science support, FIFA's "The 11", high-intensity sessions, complex skills, recovery, throw-ins, sleep and alcohol. Match and Movement Analysis: zone-oriented defense, game phases, tactical interactions, dynamical systems theory, collective motion, defensive strength map, dominant region, position-specific movements, acceleration phases, taking a dive, penalty kicks, ball possession, World-Cup game-winners. Tests & Technology: anthropometric characteristics, the Yo-yo test, skill tasks, fast vs slow players, flexibility, adjusting performance indicators, sample size, percep-tions of sport science, the red team wins. KEYWORDS: AFL, association football, elite athletes, league, match analysis, rugby, soccer, tests, training.